Antibiotic resistance of Campylobacter species in a pediatric cohort study - Schiaffino F. (2019)
The Etiology, Risk Factors, and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health and Development (MAL-ED) project was carried out as a collaborative project supported by the Bill & Melinda Gates Foundation (47075), the Foundation for the National Institutes of Health, and the National Institutes of Health, Fogarty International Center. M.N.K. was additionally supported by the Sherrilyn and Ken Fisher Center for Environmental Infectious Diseases of the Johns Hopkins School of Medicine (10POS2015). F.S. was supported by FONDECYT-CONCYTEC (grant contract number 246-2015-FONDECYT), and the National Institutes of Health Fogarty Global Health Fellows Consortium comprised of Johns Hopkins University, the University of North Carolina, Morehouse University, and Tulane University (grant no. D43TW009340). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. We declare no conflict of interest.